2013
DOI: 10.1152/ajplung.00186.2013
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary veins in the normal lung and pulmonary hypertension due to left heart disease

Abstract: Tuder RM. Pulmonary veins in the normal lung and pulmonary hypertension due to left heart disease. Am J Physiol Lung Cell Mol Physiol 305: L725-L736, 2013. First published September 13, 2013 doi:10.1152/ajplung.00186.2013.-Despite the importance of pulmonary veins in normal lung physiology and the pathobiology of pulmonary hypertension with left heart disease (PH-LHD), pulmonary veins remain largely understudied. Difficult to identify histologically, lung venous endothelium or smooth muscle cells display no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…Lung samples obtained from patients with LHF placed on a ventricular assist device showed increased pulmonary vein and artery media thickening. Of interest, some patients who improved on the assist device and underwent repeat lung biopsy had a significant improvement of pulmonary vein remodeling (16). The molecular drivers of these processes remain largely unknown.…”
Section: Does the Pulmonary Venous System Play An Important Role In Pmentioning
confidence: 99%
“…Lung samples obtained from patients with LHF placed on a ventricular assist device showed increased pulmonary vein and artery media thickening. Of interest, some patients who improved on the assist device and underwent repeat lung biopsy had a significant improvement of pulmonary vein remodeling (16). The molecular drivers of these processes remain largely unknown.…”
Section: Does the Pulmonary Venous System Play An Important Role In Pmentioning
confidence: 99%
“…Recently, the ephrin B4 receptor (EphB4), a developmental venous marker, has been shown to identify pulmonary veins in adult mice 2 . However, this finding is probably not relevant to other species as careful embryologic studies in humans have demonstrated overlap of ephB4 expression between pulmonary veins and arteries and further EphB4 does not appear to be present in the pulmonary veins of the rat suggesting that EphB4 may not be a marker applicable to humans or animal species other than the mouse 5,6 . To address these challenges a study was recently undertaken to search for unique molecular markers in pulmonary veins.…”
mentioning
confidence: 87%
“…2a (please refer to Ref. #6 for details). Fluorescent-tagged solutions are perfused retrogradely via the left atrium, allowing visualization independent of location and overall structural characteristics of the pulmonary venous system.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…26 Using a rodent model, they examined the lungs in normal animals and those with pulmonary hypertension associated with LHF. A recent study sought to identify specific pulmonary venous abnormalities as they have been understudied to this point.…”
Section: Pulmonary Venous Abnormalitiesmentioning
confidence: 99%